1982
DOI: 10.1007/bf00377929
|View full text |Cite
|
Sign up to set email alerts
|

Body burden of polychlorinated biphenyls among persons employed in capacitor manufacturing

Abstract: In an effort to assess exposure among workers engaged in capacitors manufacture, PCB concentration was determined in plasma (290) and adipose tissue (61). In general, males had higher concentrations of PCBs than females. The correlation of plasma concentration (1-546 ppb) of the more highly chlorinated PCBs, which had been used in past, with total duration of employment suggested accumulation over time. The gc-ec pattern of these PCB peaks was, in most cases, characteristic of exposure to a PCB mixture with 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 11 publications
3
43
1
Order By: Relevance
“…We also determined serum concentrations of ''light'' PCBs, that is, those congeners eluting before DDE; ''heavy'' PCBs, that is, those congeners eluting after DDE; and ''occupational'' PCB congeners, as previously defined by Wolff et al (1982). Wolff M.S.…”
Section: Serum Pcb Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We also determined serum concentrations of ''light'' PCBs, that is, those congeners eluting before DDE; ''heavy'' PCBs, that is, those congeners eluting after DDE; and ''occupational'' PCB congeners, as previously defined by Wolff et al (1982). Wolff M.S.…”
Section: Serum Pcb Analysismentioning
confidence: 99%
“…Areas surrounding the plant had an average air PCB concentration of 6.2 mg/m 3 (Taylor et al, 1991), whereas ambient air concentrations in urban areas distant from the plants averaged 0.1 mg/m 3 (Kutz and Yang, 1975). Fischbein et al (1979) analyzed sera from 310 workers in these facilities in 1976 and found that they were, on average, 10-to 20-fold higher than in the general population (Wolff et al, 1982;Lawton et al, 1985). A subgroup of our cohort also had sera archived from 1976, allowing us to compare PCB concentrations and estimate their half-lives over a 28-year period.…”
Section: Introductionmentioning
confidence: 99%
“…The high performance liquid chromatography method to quantify blood harmane concentration was described previously (Louis et al, 2002;Zheng et al, 2000). Serum pesticide concentrations were determined by gas chromatography with electron capture detection following an organochlorine-specific cleanup of the lipid fraction of serum, as detailed elsewhere (Wolff et al 1991;Wolff et al 1982;Wolff et al 2005;Louis et al 2006).…”
Section: Additional Assessments Of Exposure To Neurotoxinsmentioning
confidence: 99%
“…Unfortunately, we know nothing about human excretion of the most persistent congeners in the PCB family, DDE, and the polybrominated biphenyl family. Profound difficulty in excretion of body burdens is suggested by many data sets in which mean levels increase with age or, more properly, duration of exposure (6,8,14,17,21). In this regard, the Michigan PBB cohort and Triana cohort offer unusual opportunities to study decrements in halogenated hydrocarbon concentrations over time.…”
Section: Research Directions For Population Studiesmentioning
confidence: 99%